Targeting survival and cell trafficking in multiple myeloma and Waldenstrom macroglobulinemia using pan‐class I PI3K inhibitor, buparlisib. Issue 11 (12th August 2014) - Sahin, Ilyas; Azab, Feda; Mishima, Yuji; Moschetta, Michele; Tsang, Brian; Glavey, Siobhan V.; Manier, Salomon; Zhang, Yu; Sacco, Antonio; Roccaro, Aldo M.; Azab, Abdel Kareem; Ghobrial, Irene M.
<x xml:space="preserve">Abstract</x> The phosphatidylinositol‐3 kinase (PI3K) pathway is activated in multiple myeloma (MM) and Waldenstrom Macroglobulenima (WM), and plays a crucial role in tumor progression and drug resistance. In this study, we characterized the role of pan‐class I PI3K inhibition on cell trafficking and survival of MM and WM cells. We tested the effect of pan‐class I PI3K inhibition by siRNA silencing or pharmacologic inhibition with buparlisib on MM cell survival, apoptosis and cell cycle in vitro and tumor growth and mobilization of MM cells in vivo. We then evaluated buparlisib‐dependent mechanisms of induced MM cell mobilization. Moreover, the effect of buparlisib on cell survival, apoptosis, and adhesion of WM cells to bone marrow stromal cells (BMSCs) has been evaluated. We showed that buparlisib induced toxicity in MM cells, supported by induction of apoptosis and cell cycle arrest. Buparlisib was also found to reduce tumor progression in vivo. Importantly, buparlisib enhanced MM cell mobilization in vivo which was driven by decreased adhesion of MM cells to BMSCs and increased chemotaxis via up‐regulation of CXCR4 expression. Similar to its effects on MM cells, buparlisib also induced cell survival and apoptosis, and decreased adhesion in WM cells. These data highlight the critical contribution of class I PI3K signaling to the regulation of survival and cell dissemination in B‐cell malignancies. Am. J. Hematol. 89:1030–1036, 2014. © 2014 Wiley Periodicals, Inc.